2007
DOI: 10.1016/j.bbrc.2006.12.097
|View full text |Cite
|
Sign up to set email alerts
|

Human SLUG does not directly bind to CtBP1

Abstract: SLUG is a transcriptional repressor protein implicated to have major role in the oncogenesis and metastasis of human breast cells. We previously have shown by chromatin immunoprecipitation assay that human SLUG (hSLUG) is co-localized with the co-repressor protein CtBP1 as bound to the BRCA2 gene silencer. hSLUG was predicted to be binding directly to CtBP1 because of an apparent presence of CtBP1 binding site in its amino acid sequences. Here, we provide evidence through yeast two-hybrid and in vitro co-immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The biochemical role of this motif of SLUG in its repressor activity is not known. We found that although this motif has similarity with the classical CtBP1 binding sequence (41,42), this sequence of SLUG is not responsible for CtBP1 binding (43). 3 Our study also reflects upon the importance of E2-box binding of SLUG and its repressor activity.…”
Section: Discussionmentioning
confidence: 55%
“…The biochemical role of this motif of SLUG in its repressor activity is not known. We found that although this motif has similarity with the classical CtBP1 binding sequence (41,42), this sequence of SLUG is not responsible for CtBP1 binding (43). 3 Our study also reflects upon the importance of E2-box binding of SLUG and its repressor activity.…”
Section: Discussionmentioning
confidence: 55%
“…According to this model, SLUG is recruited to any or all three of the E2-box sequences at the VDR gene promoter through its DNA binding domain. We have shown previously that hSLUG cannot directly bind to CtBP1 [13]. Thus, assisted perhaps by other transcription regulator(s), CtBP1 is recruited at the P-motif of SLUG.…”
Section: In Vivo Binding Of Slug Ctbp1 and Hdac1 Proteins To The Vdrmentioning
confidence: 94%
“…Protein extracts were made and Western blotting was performed as described [21, 23]. Cell lysates containing equal amounts of protein were resolved by 4–12% SDS–PAGE, transferred to nitrocellulose membranes, probed with the appropriate antibodies, and detected by means of enhanced chemiluminescence [21, 22]. …”
Section: Methodsmentioning
confidence: 99%